New Torrenticola piersig (Acari: Hydrachnidia: Torrenticolidae) species for the Turkish fauna - Pesic, Vladimir; Erman, Orhan; Esen, Yunus (My University, 2006)
In this study, the morphological characteristics, measurements, habitats and distribution of Torrenticola nana Di Sabatino & Gerecke 2003 and Torrenticola Jasminae Bader, 1988, which are new records for the Turkish fauna, are presented. © TÜBİTAK.
Keywords: New records; Running water; Torrenticola; Turkey; Water mites